Upgrade of the cedit database of earthquake-induced ground effects in Italy - Caprari, Patrizia; Della Seta, Marta; Martino, Salvatore; Fantini, Andrea; Fiorucci, Matteo; Priore, Tiziana (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value=""1":2,"2":"The database related to the Italian Catalogue of Earthquake- Induced Ground Failures (CEDIT), was recently upgraded and updated to 2017 in the frame of a work-in-progress focused on the following issues: i) reorganization of the geo-database architecture; ii) revision of the earthquake parameters from the CFTI5 e CPTI15 catalogues by INGV; ii) addition of new data on effects induced by earthquakes occurred from 2009 to 2017; iv) attribution of macroseismic intensity value to each effect site, according to the CFTI5 e CPTI15 catalogues by INGV. The revised CEDIT database aims at achieving: i) the optimization of the CEDIT catalogue in order to increase its usefulness for both Public Institutions and individual users; ii) a new architecture of the geo-database in view of a future implementation of the online catalogue which implies its usability via web-app also to support post-event detection and surveying activities. Here we illustrate the new geo-database design and discuss the statistics that can be derived from the updated database. Statistical analysis was carried out on the data recorded in the last update of CEDIT to 2017 and compared with the analysis of the previous update outline that: - the most represented ground effects are the landslides with a percentage of 55% followed by ground cracks with a percentage of 23%; - the MCS intensity (IMCS) distribution of the effect sites shows a maximum in correspondence of the IMCS class 8 even if a second frequency peak appears in the IMCS class 7 only for surface faulting effects; - the distribution of the effects according to the epicentral distance shows a decrease for all the typologies of induced ground effects with increasing epicentral distance."" data-sheets-userformat=""2":15233,"3":"1":0,"10":1,"11":3,"12":0,"14":"1":2,"2":0,"15":"Arial","16":8">The database related to the Italian Catalogue of Earthquake- Induced Ground Failures (CEDIT), was recently upgraded and updated to 2017 in the frame of a work-in-progress focused on the following issues: i) reorganization of the geo-database architecture; ii) revision of the earthquake parameters from the CFTI5 e CPTI15 catalogues by INGV; ii) addition of new data on effects induced by earthquakes occurred from 2009 to 2017; iv) attribution of macroseismic intensity value to each effect site, according to the CFTI5 e CPTI15 catalogues by INGV. The revised CEDIT database aims at achieving: i) the optimization of the CEDIT catalogue in order to increase its usefulness for both Public Institutions and individual users; ii) a new architecture of the geo-database in view of a future implementation of the online catalogue which implies its usability via web-app also to support post-event detection and surveying activities. Here we illustrate the new geo-database design and discuss the statistics that can be derived from the updated database. Statistical analysis was carried out on the data recorded in the last update of CEDIT to 2017 and compared with the analysis of the previous update outline that: - the most represented ground effects are the landslides with a percentage of 55% followed by ground cracks with a percentage of 23%; - the MCS intensity (IMCS) distribution of the effect sites shows a maximum in correspondence of the IMCS class 8 even if a second frequency peak appears in the IMCS class 7 only for surface faulting effects; - the distribution of the effects according to the epicentral distance shows a decrease for all the typologies of induced ground effects with increasing epicentral distance.